1997
DOI: 10.1016/s0960-9822(06)00026-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of components of the extracellular matrix on differentiation and apoptosis

Abstract: Cellular responses to ECM are mediated by the combined action of macromolecular constituents and regulatory molecules, such as bFGF, that are sequestered and stored in the ECM. ECM or laminin protects against cell death by interacting with specific integrin receptors and maintaining a well-developed actin cytoskeleton. ECM-bound bFGF provides differentiation signals for granulosa cells, which are in intimate contact with the ECM. Thus, a clear distinction can be made between the survival activity and the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
1
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 53 publications
4
69
1
2
Order By: Relevance
“…It is well established that the loss of cell attachment to ECM causes apoptosis, according to a process named anoikis (Ruoslahti & Reed 1994, Giancotti & Ruoslahti 1999. The present result is consistent with previous data showing that LN enhances cell survival in rat (Aharoni et al 1996) and ovine GC (Huet et al 2001). In vitro, histological observations have established that GC adjacent to the follicular basement membrane are protected from entering apoptosis in early atretic follicles (Monniaux et al 1999).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…It is well established that the loss of cell attachment to ECM causes apoptosis, according to a process named anoikis (Ruoslahti & Reed 1994, Giancotti & Ruoslahti 1999. The present result is consistent with previous data showing that LN enhances cell survival in rat (Aharoni et al 1996) and ovine GC (Huet et al 2001). In vitro, histological observations have established that GC adjacent to the follicular basement membrane are protected from entering apoptosis in early atretic follicles (Monniaux et al 1999).…”
Section: Discussionsupporting
confidence: 82%
“…In vitro, purified LN used as a culture substratum improves GC survival in rat (Aharoni et al 1996) and sheep (Huet et al 2001) and stimulates their proliferation in sheep (Huet et al 2001). However, the effects of LN on GC steroidogenesis are still the object of controversy since LN enhances P4 secretion in rat (Aten et al 1995, Aharoni et al 1996 and pig (Sites et al 1996), but inhibits it in human . Moreover, the functional importance of LN in GC differentiation to an E2-secreting cell type during terminal follicular development, and then to a P4-secreting cell type during the luteinization process has not been established.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of integrins has been reported as crucial for maintenance of beta-cell viability and differentiation [13,18,30,31,32]. Studies from our own group have further demonstrated the specific role of integrins α3β1 and α6β1 on rat beta cells [12,33].…”
Section: Discussionmentioning
confidence: 70%